A Practical Guide to Healthy Living - Wendy Lynch; Annie Wallau; Melanie Thomas; Wendy Mussoline; Catherine Campbell (EDIS)
This publication provides a guide to implementing healthy living and wellness practices. Written by Wendy W. Lynch, Annie Wallau, Melanie Thomas, Wendy Mussoline, and Catherine Campbell, and published by the UF/IFAS Department of Family, Youth and Community Sciences, September 2021.